Bandwidth and gain enhancement of composite right left handed metamaterial transmission line planar antenna employing a non foster impedance matching circuit board - Mohammad Alibakhshikenari (Nature Portfolio, 2021)
Abstract The paper demonstrates an effective technique to significantly enhance the bandwidth and radiation gain of an otherwise narrowband composite right/left-handed transmission-line (CRLH-TL) antenna using a non-Foster impedance matching circuit (NF-IMC) without affecting the antenna’s stability. This is achieved by using the negative reactance of the NF-IMC to counteract the input capacitance of the antenna. Series capacitance of the CRLH-TL unit-cell is created by etching a dielectric spiral slot inside a rectangular microstrip patch that is grounded through a spiraled microstrip inductance. The overall size of the antenna, including the NF-IMC at its lowest operating frequency is 0.335λ0 × 0.137λ0 × 0.003λ0, where λ0 is the free-space wavelength at 1.4 GHz. The performance of the antenna was verified through actual measurements. The stable bandwidth of the antenna for |S11|≤ − 18 dB is greater than 1 GHz (1.4–2.45 GHz), which is significantly wider than the CRLH-TL antenna without the proposed impedance matching circuit. In addition, with the proposed technique the measured radiation gain and efficiency of the antenna are increased on average by 3.2 dBi and 31.5% over the operating frequency band.